PENGARUH MODEL CORE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS MATERI PERUBAHAN WUJUD BENDA DI KELAS IV SDIT AL HABIB - Della Pradita; Sujarwo; Safrida Napitupulu; Dara Fitrah Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' critical thinking skills in Science and Social Studies (IPAS) learning on the topic of changes in the states of matter are still relatively low due to teacher-centered learning practices. This study aimed to determine the effect of the CORE (Connecting, Organizing, Reflecting, and Extending) learning model on the critical thinking skills of fourth-grade students at SDIT Al Habib. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 47 students, including 23 students in the experimental class and 24 students in the control class. Data were collected through pretests and posttests measuring students' critical thinking skills. The results showed that the experimental class experienced a significant improvement, with the mean score increasing from 41.70 on the pretest to 82.17 on the posttest and a mastery level of 82.61%. In contrast, the control class improved from 41.70 to 55.83, with a mastery level of 20.83%. The Independent Samples t-Test yielded a significance value of 0.000 < 0.05, indicating a significant effect of the CORE learning model on students' critical thinking skills. Therefore, it can be concluded that the CORE learning model significantly improves students' critical thinking skills in learning about changes in the states of matter. The model is recommended as an alternative instructional approach for enhancing critical thinking skills in elementary schools